Enhancer RNAs: mechanisms in transcriptional regulation and functions in diseases - Qianhui Li; Xin Liu; Jingtao Wen; Xi Chen; Bumin Xie; Yang Zhao (Cell Communication and Signaling, 2023)
Abstract In recent years, increasingly more non-coding RNAs have been detected with the development of high-throughput sequencing technology, including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), circular RNAs (circRNAs), small nucleolar RNAs (snoRNAs), and piwi-interacting RNA (piRNAs). The discovery of enhancer RNAs (eRNAs) in 2010 has further broadened the range of non-coding RNAs revealed. eRNAs are non-coding RNA molecules produced by the transcription of DNA cis-acting elements, enhancer fragments. Recent studies revealed that the transcription of eRNAs may be a biological marker responding to enhancer activity that can participate in the regulation of coding gene transcription. In this review, we discussed the biological characteristics of eRNAs, their functions in transcriptional regulation, the regulation factors of eRNAs production, and the research progress of eRNAs in different diseases. Video Abstract